Assessment of passenger satisfaction in rail transportation in Sri Lanka: A case study on the coastal line from Panadura to Colombo - Jayarathna, C.N.; Danthanarayana, C. T. (University of Colombo, Sri Lanka., 2019)
Rail transportation in Sri Lanka is government-owned and the one and only massive passenger and freight transport service, identified as an economical and eco-friendly public transport mode. The quality of rail transportation is deteriorating due to the ageing fleet and lack of infrastructure facilities. Upgrading rail transportation is imperative to attract more passengers and determining the factors of passenger satisfaction is a key element to increase the existing rail transport modal share which accounts for 5% of total motorised transportation. The focus of this study is to ascertain the qualitative factors influencing passenger satisfaction in rail transportation, and the coastal railway line from Panadura to Colombo was selected as the case for this study. The study was conducted using primary data which was collected through a structured questionnaire and 150 passengers were selected as the sample. An interview-based survey method was used to collect data and a five-point Likert scale was used in the rating of the questions. 20 service quality factors represented by three aspects - railway stations and platforms, ticketing process, and train service - were considered for this study. The descriptive analysis showed passengers as dissatisfied with the overall service quality of the Panadura-Colombo coastal line railway transportation. Among the overall quality factors, passengers were highly dissatisfied with refreshment facilities, toilet, and waiting room facilities provided in the stations and platforms, and storage facilities available in trains, compared to the other quality factors. The government should implement proper transport policies to upgrade and maintain the standard of facilities with a reasonable fare structure while ensuring a clean and attractive environment in stations, platforms, and inside the trains, to enhance service quality. Further studies need to be conducted comprehensively to evaluate passenger satisfaction in the entire coastal line from Colombo to Matara and Beliatta to generalise the survey results.
Keywords: satisfaction, quality factors, rail transport, service quality